Risk-based Maintenance Model for Road Network - Sulistyowati Sulistyowati; Ummi Chasanah (International Conference on Coastal and Delta Areas, 2017)
Road is an asset for a country to develop. To be able to serve until its planned service period road needs maintenance. On the other hand maintenance does needs budget to deal with. As budget for maintenance is limited, cost optimization becomes very important. This research used risk-based maintenance model and multi-criteria decision making and weight method for a road network. For this study we chose a road network comprised of seven roads. The road network comprised of jl. Sirodjuddin, jl. Prof. Sudharto, jl. Setiabudi, jl. Gombel Lama, jl. Gombel, jl. Teuku Umar and jl. Dr. Wahidin. The data we needed came from assessing each road’s surface condition and questionnaire where some professionals in civil engineering actively involved. From the data we gained and analysed, we found a risk category for each road. From the risk category we would be able to develop maintenance action plan for each road. Based on the maintenance action plan, cost optimisation will be achieved. Keywords : road maintenance, risk-based maintenance model, road network, analytical hierarchy process